Long COVID: A Systematic Review of Preventive Strategies - Sun O. Park; Neha Nanda (Infectious Disease Reports)
Background: Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019, long COVID (LC) has become a significant global health burden. While knowledge about LC is accumulating, studies on its prevention are still lacking. Methods: We conducted a systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to investigate prevention options for LC. We identified fifteen articles on vaccines, seven on antivirals, and six on other interventions after searching for articles in the PubMed/MEDLINE database using the MeSH terms. Results: Most vaccine-related studies demonstrated a protective effect of COVID-19 vaccines against developing LC. Our review found an equivocal effect of antivirals, while metformin had a protective effect in outpatients and corticosteroids were protective in hospitalized patients against LC. Conversely, COVID-19 convalescent plasma and multiple micronutrient supplement did not confer any protection against LC. Conclusions: COVID-19 vaccination is vital as it not only prevents COVID-19 but also reduces the severity of illness and may help prevent LC. Further studies are warranted to shed light on preventive strategies for long COVID.